2021
DOI: 10.56899/150.6b.02
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Nutritional Status of School-aged Children Belonging to Farming Households in the Philippines

Abstract: Undernutrition among school-aged children continues to be a public health concern in the Philippines, where agriculture is the primary source of income. School-age is a crucial phase of development and growth among children since it can establish nutritional knowledge and healthy eating habits across the next life stages. Evidence suggested that undernutrition exists among school-aged children belonging to households relying on agriculture. This study aims to identify factors affecting the nutritional status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…This study revealed a statistically significant association between the wealth index (WI) and wasting among school-age children, which aligns with previous findings in the Philippines [52], and South Ari District in Southern Ethiopia [53]. Furthermore, the odds of wasting were significantly lower for children aged 11-14 years compared to those aged 6-10 years, which is consistent with studies conducted in Gondar town, northwestern Ethiopia [32], Gedeo Zone in South Ethiopia [48], Northern Sri Lanka [51], the Philippines [52], and North East of Morocco [54]. Additionally, children who consumed four or more food groups had lower odds of wasting, as supported by similar studies conducted in the Semien Bench district in Ethiopia [55], and rural Bangladesh [56].…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed a statistically significant association between the wealth index (WI) and wasting among school-age children, which aligns with previous findings in the Philippines [52], and South Ari District in Southern Ethiopia [53]. Furthermore, the odds of wasting were significantly lower for children aged 11-14 years compared to those aged 6-10 years, which is consistent with studies conducted in Gondar town, northwestern Ethiopia [32], Gedeo Zone in South Ethiopia [48], Northern Sri Lanka [51], the Philippines [52], and North East of Morocco [54]. Additionally, children who consumed four or more food groups had lower odds of wasting, as supported by similar studies conducted in the Semien Bench district in Ethiopia [55], and rural Bangladesh [56].…”
Section: Discussionsupporting
confidence: 91%
“…However, this was not observed across low and middle-income countries including Sub-Saharan Africa and Southeast Asia as reflected by the sustained high rates of hunger, food insecurity, and undernutrition among children (Heidkamp et al 2021). This public health concern is also an issue in the Philippines, particularly in households relying on agriculture (FNRI 2016;Capanzana et al 2018;dela Luna and Talavera 2021).…”
Section: Introductionmentioning
confidence: 99%